Green Zinc Oxide-based Photocatalysts: Preparation, Characterization And Photocatalytic Study For The Degradation Of Dyes Under Visible Light Irradiation - Abdullah, Fatin Hazirah (2023)
There is a scarcity of literature on the fabrication of zinc oxide (ZnO) photocatalyst using a greener biosynthetic route and bio-based materials, with a primary focus on improving the reusability, collection, and recovery of the photocatalyst. Besides, ZnO suffers from low photodegradation efficiency due to low visible light absorption and high recombination of photogenerated charge carriers. In this study, green ZnO-based photocatalysts were successfully synthesized at room temperature using environmentally friendly, low cost, and facile methods. The work highlights the combination of valorization of banana peel (BP) waste and natural rubber (NR) biopolymer to develop effective, economic, and sustainable photocatalysts with good reusability for high removal of dyes. The photoactivity of these photocatalysts were evaluated by the degradation of Methylene Blue (MB) dye under visible light irradiation. The ZnO nanoparticles were initially synthesized using BP extract as reducing and capping agents. The best conditions for green synthesis of ZnO were pH 12, 1 mL BP extract, 0.02 M zinc acetate dihydrate, 3 h synthesis time, and 60 °C temperature. The biosynthesized ZnO exhibited advanced properties and superior photocatalytic performance than the chemically synthesized ZnO, which was prepared for comparison purposes.